Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat pada Pasien Tuberkulosis (TBC) di Puskesmas Kediri - Niswatun Fahmi (Gema Cendekia Institute, 2025)
Tuberculosis (TB) remains one of the major public health problems in Indonesia. The success of TB treatment largely depends on the level of patient adherence to taking anti-tuberculosis drugs (OAT) regularly and completely. However, poor adherence often becomes the main obstacle in achieving optimal recovery. One of the key factors suspected to influence adherence is the patient’s level of knowledge regarding TB and its treatment. This study aimed to analyze the relationship between knowledge level and medication adherence among TB patients undergoing treatment at the Kediri Public Health Center, West Lombok Regency. This research employed a descriptive correlational design with a cross-sectional approach. The study population consisted of all TB patients who were actively undergoing treatment during the period of January–June 2025. The sample was determined using a purposive sampling technique, resulting in 60 respondents. The instruments used were a validated and reliable questionnaire assessing knowledge about TB and the Morisky Medication Adherence Scale (MMAS-8) to measure medication adherence. Data analysis was conducted using univariate and bivariate tests, with the Chi-square test applied at a significance level of α = 0.05. The results showed that the majority of respondents had a good level of knowledge (56.7%) and a high level of adherence (61.7%). Statistical analysis revealed a significant relationship between the level of knowledge and medication adherence among TB patients (p = 0.021). These findings indicate that adequate knowledge about TB and its treatment benefits can enhance patients’ adherence to OAT therapy. The study recommends that nursing personnel strengthen continuous educational interventions through both individual and group counseling approaches to improve TB patients’ knowledge and motivation in completing their treatment regimen.